Correlation Analysis of Activity Levels and Risk Factors in Patients with Stroke: Variations in Cardiac Function According to the Longshi Scale - Wang Y; Lv H; He M; Wu P; Li F; Wang Y (Journal of Multidisciplinary Healthcare, 2024)
Yao Wang,1,* Huilan Lv,1,* Mingjun He,1 Peishan Wu,1 Fei Li,1 Yulong Wang2 1Department of Rehabilitation Medicine, Dapeng New District Nan’ao People’s Hospital, Shenzhen, 518121, People’s Republic of China; 2Department of Rehabilitation, The Second People’s Hospital of Shenzhen, The First Affiliated Hospital of Shenzhen University, Shenzhen, 518035, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yulong Wang, Department of Rehabilitation, The Second People’s Hospital of Shenzhen; the First Affiliated Hospital of Shenzhen University, No. 3002, Sungang Road, Futian District, Shenzhen, 518035, People’s Republic of China, Tel +86 139 2344 8395, Fax +86 0755 83366388, Email wangy12013054@163.comObjective: This study examined the link between physical activity levels, as measured by the Longshi Scale, and cardiac function and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels in stroke patients, aiming to find correlations with stroke risk factors.Methods: The study involved 123 apoplexy patients divided into four groups based on the Longshi Scale: bedridden (31), domestic (32), community (30), and health (30). Clinical data was collected, and hemodynamic assessments were performed using impedance cardiography.Results: Cardiac output time index (CTI) and estimated ejection fraction (EF est) were significantly reduced in both the domestic and community groups compared to the health group (P < 0.05), while diastolic arterial blood pressure (DABP) and systemic vascular resistance index (SVRi) were increased. In the bedridden group, stroke volume (SV), cardiac output (CO), CTI, left cardiac work index (LCWi), and EF est were all lower compared to the health group (P < 0.05), with SVRI and NT-proBNP levels being higher. Additionally, the bedridden group exhibited lower SV, CO, DABP, LCWi, CTI, and EF est when compared to the domestic and community groups (P < 0.05), but higher end-diastolic filling rate (EDFR) and NT-proBNP levels. The Longshi Scale grading positively correlated with SV (r = 0.536, P < 0.01), and NT-proBNP, EF, and cognitive dysfunction were found to be associated with activity levels in stroke patients.Conclusion: The Longshi Scale correlates with cardiac function indicators like NT-proBNP and EF, and can help identify stroke patients at risk of cardiac dysfunction. Moreover, cognitive dysfunction was identified as a significant factor influencing the range of activity in patients with stroke.Keywords: assessment, hemodynamic, Longshi Scale, stroke